Constitutional nationalism and legal exclusion equality, identity politics, and democracy in Nepal (1990-2007) - Malagodi, Mara. (Oxford : Oxford University Press, 2013)
This book investigates the relationship between constitutional nationalism and patterns of legal exclusion during the 1990 constitutional experience of Nepal, focusing on the institutional management of socio-cultural diversity by the state in the context of post-Cold War re-democratization and the outcome of such strategy.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Keywords: Nepal -- Politics and government -- 1990-; Constitutional law -- Nepal; Nepal -- Social conditions -- 20th century; Nepal -- Social conditions -- 21st century; Marginality, Social -- Nepal